PERANCANGAN SISTEM INFORMASI PENGELOLAAN IURAN ANGGOTA KONGREGASI MSC BERBASIS WEBSITE - Nicholaus Jamrewav; Ria Manurung; Romanus Edy Prabowo (Electro Luceat, 2025)
The emergence of information technology has impacted many organisations, which have utilised it to become more efficient and accurate in financial management, including recording membership fees. The MSC Community Organisation of Central Java and South Kalimantan still uses a manual method based on Microsoft Office to record and report membership fees. This causes problems in producing accurate financial reports, as well as the possibility of recording errors and duplicate data. The purpose of this research is to develop an online information system for managing contributions. During the system design process, developers and users can interact directly through the Prototype System Development Life Cycle (SDLC) model. This system was developed using the Django framework and features key components, including a dashboard for real-time financial information, member data management, contribution transaction tracking, and automated monthly and annual report generation. The implementation results show that this system can improve the efficiency and transparency of the organisation's financial management. Therefore, the information system serves as an essential tool for treasurers and members to monitor contributions in an integrated and easy manner. Suggestions for further system development include incorporating payment notification features and integrating digital payment methods.